QKAT: a high-throughput qPCR method for KIR gene copy number and haplotype determination. Issue 1 (December 2016) - Jiang, W.; Johnson, C.; Simecek, N.; López-Álvarez, M.; Di, D.; Trowsdale, J.; Traherne, J.
Abstract Killer cell immunoglobulin-like receptors (KIRs), expressed on natural killer cells and T cells, have considerable biomedical relevance playing significant roles in immunity, pregnancy and transplantation. TheKIR locus is one of the most complex and polymorphic regions of the human genome. Extensive sequence homology and copy number variation makesKIR s technically laborious and expensive to type. To aid the investigation ofKIR s in human disease we developed a high-throughput, multiplex real-time polymerase chain reaction method to determine gene copy number for eachKIR locus. We used reference DNA samples to validate the accuracy and a cohort of 1698 individuals to evaluate capability for precise copy number discrimination. The method provides improved information and identifiesKIR haplotype alterations that were not previously visible using other approaches.